A 2:1 atrioventricular block in an adult patient with a Fontan circulation: from transesophageal pacing to echocardiographic guidance of epicardial pacemaker lead placement - Jeff M. Smit; Madelien V. Regeer; Adrianus P. Wijnmaalen; Monique R.M. Jongbloed; Mark G. Hazekamp; Anastasia D. Egorova (International Journal of Cardiology Congenital Heart Disease)
Background: The diagnosis and management of atrioventricular (AV)-conduction disorders in patients with a Fontan circulation can be challenging. Little is known about the effects of various pacing strategies in single-ventricle patients. Here we report 1) the feasibility of transesophageal electrophysiological study (EPS) to assess AV-conduction in a patient with limited venous access and 2) the potential of echocardiography to guide epicardial systemic right ventricular (sRV) lead positioning and to evaluate the hemodynamic consequences of sRV pacing in order to mitigate long-term effects of single site ventricular pacing. Material and methods: A 21-year old male with hypoplastic left heart syndrome, palliated with Norwood and Glenn procedures, and ultimately extracardiac total cavopulmonary connection was seen for a regular check-up. He reported difficulty cycling against the wind. During exercise stress test, a 2:1 AV-block occurred at atrial frequencies >100 bpm with recovery of 1:1 AV-conduction at sinus rates of 80–100 bpm. In order to discriminate between a 2:1 conducted atrial tachycardia and an impaired anterograde AV-conduction during sinus rhythm in the setting of bilateral femoral vein and unilateral subclavian/jugular vein occlusion, EPS by transesophageal pacing was proposed. Results: Bipolar transesophageal pacing of the left atrium confirmed an anterograde AV-Wenckebach point at 103 bpm, confirming the indication for AV-sequential pacing. Epicardial leads were surgically placed on the atrium and sRV apex. During intraoperative sRV pacing, transesophageal echocardiography confirmed the ventricular contraction pattern to remain synchronous with stable estimated cardiac output. Transthoracic echocardiography was performed postoperatively to assess the effects of sRV pacing on ventricular (dys)synchrony, systolic function and estimated cardiac output. These parameters remained unchanged during sRV pacing, compared to intrinsic conduction, an important finding in light of preserving sRV function. Conclusions: EPS to assess AV conduction could safely be performed by transesophageal pacing in this patient with Fontan circulation. Moreover, echocardiographic guidance of epicardial sRV pacemaker lead placement was feasible and may help to define the optimal pacing site in Fontan patients.